Security Audit and Analysis of High School Websites Using Cross Site Scripting (XSS) Method and Insecure Direct Object Reference (IDOR) Penetration Test - Muhammad Kholilul Adrian; Raphael Bianco Huwae; Ahmad Zafrullah Mardiansyah (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2025)
This study investigates security vulnerabilities in secondary school PPDB websites, focusing on Structured Query Language (SQL) Injection and Cross Site Scripting (XSS) techniques. The research aims to conduct a security audit and analysis using XSS methods and Insecure Direct Object References (IDOR) penetration tests. The primary objectives are to identify existing security gaps, provide recommendations for improvement, and enhance the overall security of these websites. By addressing these vulnerabilities, the study seeks to make PPDB websites more secure and reliable in protecting users' personal data and maintaining system integrity. Additionally, this research aims to raise awareness among PPDB system managers and schools about the importance of cybersecurity in website development and management, offering practical solutions and serving as a reference for improving website security in the educational sector.